PREDICTING PURCHASE INTENTION TOWARD HALAL PACKAGED FOOD FROM NON-MUSLIM MANUFACTURERS: A COMPARATIVE STUDY OF MUSLIM IN THAILAND AND INDONESIA - Athapol Ruangkanjanases; Tassaya Sermsaksopon (Bina Nusantara University, 2019)
Halal packaged food products have attracted much attention in ASEAN where its largest member, Indonesia, is the world’s most populous Muslim country and is a major market in the region. For non-Muslim country like Thailand, Islam also has significant role being the second popular religion after Buddhism. Although Islamic population in Thailand is not as great as in Islamic countries, Thailand plays a substantial part in halal business as beingrecognized as a food production base exporting halal food worldwide. Therefore, the major objective of this study is to identify and analyze the significant factors that influence purchase intention of Thai and Indonesian Muslims toward halal packaged food products from non-Muslim manufacturers. This study used a survey to collect data consisting of 200 Thai respondents and 200 Indonesian respondents. The results indicated that product ingredients significantly influenced consumers’ intention to purchase both in Thailand and Indonesia while halal certification only significantly influenced consumers’ intention to purchase in Indonesia.